LINGUACULTURAL PECULIARITIES OF THE CONCEPT “HAPPINESS” IN ENGLISH AND UZBEK LANGUAGES - Ashurova, Maftuna (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In modern linguistics, there are no cases of comprehensive study of concepts, that is, the study of both theoretical and practical aspects. Thus, it is not an easy task to determine the ways of lexical expression of a certain concept. The purpose of this article is to identify stereotypes related to the concept of happiness in the linguistic culture of the Uzbek and English languages, to study the linguistic space, as well as to analyze some literary sources. This article is devoted to the linguacultural aspects of concept “happiness” in modern English and Uzbek languages. Furthermore, it is analyzed both as common value of humankind as well as cultural specify of some nation. Attitude to happiness allows revealing the existential characteristics, norms, traditions of different social groups, since a different interpretation of happiness within the framework of different cultures reveals their ethnos cultural specificity and perception of the world and people.